RetroScan: An Easy-to-Use Pipeline for Retrocopy Annotation and Visualization - Wei, Zhaoyuan; Sun, Jiahe; Li, Qinhui; Yao, Ting; Zeng, Haiyue; Wang, Yi (Frontiers in Genetics, 2021)
Retrocopies, which are considered "junk genes", are occasionally formed via the insertion of reverse-transcribed mRNAs at new positions in the genome. However, an increasing number of recent studies have shown that some retrocopies exhibit new biological functions and may contribute to genome evolution. Hence, the identification of retrocopies has become very meaningful for studying gene duplication and new gene generation. Current pipelines identify retrocopies through complex operations using alignment programs and filter scripts in a step-by-step manner. Therefore, there is an urgent need for a simple and convenient retrocopy annotation tool. Here, we report the development of RetroScan, a publicly available and easy-to-use tool for scanning, annotating and displaying retrocopies, consisting of two components: an analysis pipeline and a visual interface. The pipeline integrates a series of bioinformatics software programs and scripts for identifying retrocopies in just one line of command. Compared with previous methods, RetroScan increases accuracy and reduces false-positive results. We also provide a Shiny app for visualization. It displays information on retrocopies and their parental genes that can be used for the study of retrocopy structure and evolution. RetroScan is available at https://github.com/Vicky123wzy/RetroScan.